Impact of Cytomegalovirus on Long-term Mortality and Cancer Risk After Organ Transplantation. Issue 9 (September 2015) - Desai, Rajeev; Collett, Dave; Watson, Christopher J. E.; Johnson, Philip J.; Moss, Paul; Neuberger, James
<x xml:space="preserve">Abstract</x> Background There is conflicting evidence of the effect of cytomegalovirus (CMV) infection on survival and the risk of cancer after transplantation. Methods All recipients of kidney, liver, heart, and lung transplants in the United Kingdom between 1987 and 2007 with known CMV immunoglobulin G status were identified from the U.K. Transplant Registry. Based on the donor-recipient CMV status, recipients were grouped into: donor (D) negative recipient (R) negative (D− R−), D−R+, D + R+ and D + R−. Cancer data were obtained from the Office for National Statistics. The impact of CMV infection on survival and cancer incidence was assessed. Results The 10-year posttransplant survival in D−R− recipients (73.6% [95%CI, 72.3, 74.9]) was significantly higher (P < 0.0001) than in other recipients (66.1% [65.3, 66.9]). Compared with the D− R− group, the risk-adjusted hazard of death within 10 years of transplantation for D+ R− group was 14% higher for kidney recipients (P = 0.0495), 13% higher for liver recipients (P = 0.16), 34% higher for heart recipients (P = 0.01), and 35% higher for lung recipients (P = 0.006). The proportion of recipients with a cardiovascular cause of death was higher (P = 0.03) among the recipients exposed to CMV (18%) as compared to the D− R− recipients (16%). The CMV status was not associated with an increased risk of cancer. Conclusions The results from this large study demonstrate that CMV is associated with a significantly increased long-term mortality in kidney and cardiothoracic transplant recipients and an increased risk of cardiovascular death but not of posttransplant cancer.